11.3% efficient planar Si-PEDOT : PSS hybrid solar cell with a thin interfacial oxide - He, Lining (2013)
Hybrid solar cells are fabricated based on heterojunction between planar n-type Si and a p-type polymer, poly (3,4-ethylene-dioxythiophene): polystyrenesulfonate (PEDOT: PSS). The effect of hydrogen-terminated (H-Si) and oxide-terminated (SiOx-Si) Si surface on the cell performance are investigated. Compared to cells with H-Si surface that exhibits a power conversion efficiency (PCE) of 0.04%, the PCE of the cells with SiOx-Si surface is boosted significantly to 11.3%. It is also found that the SiOx-Si cell exhibits a much better diode rectifying behavior and the SiOx-Si surface bonding results in a favorable band alignment in the Si/PEDOT interface for photo-excited carrier separation.